Thymic Extranodal Marginal-Zone Lymphoma of Mucosa-Associated Lymphoid Tissue: Pathological Features, 18F-FDG PET/CT Findings and Prognosis in 12 Cases - Zang, Shengbing; Liu, Lei; Bao, Junjie; Xiong, Min; Zhao, Yumo; Lin, Suxia; Lin, Xiaoping (Frontiers in Medicine, 2022)
Purpose: Primary thymic extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue (MALT) lymphoma is a rare type of MALT lymphoma. We aim to investigate the clinicopathologic features, 18F-FDG PET/CT findings and outcome for patients with primary thymic MALT lymphoma; to explore the correlation between metabolic parameters and immunohistochemical phenotypes. Methods: A retrospective single-center study enrolled 12 patients with primary thymic MALT lymphoma between 2010 and 2021. A total of 19 18F-FDG PET/CT scans were performed, and clinicopathologic and immunohistochemical characteristics, PET/CT imaging features, and outcomes were analyzed. Results: The male-to-female ratio was 1. The median age at diagnosis was 40 (range 31–68). The long diameter of the lesions ranges from 3.5 to 15.7. Histopathological examinations revealed the normal thymic lobular architecture is effaced by a diffuse lymphoid infiltrate, but residual Hassall corpuscles can still be identified, mostly with CD20+, PAX5+, CD3-, CD23-, CD10-, BCL-6- , cyclin D1-, EBER- and low Ki-67. The gene rearrangement indicated that IGH gene but not TCR gene found in 7 patients. At six initial PET/CT scans, mean SUVmax = 6.8 (range, 3.1–12.4), mean MTV = 40.0 (range, 6.7–81.4), mean TLG = 144.3 (range, 19.7–286.4). During the follow-up period, there was no death except for the patient with DLBCL who died 59 months after diagnosis of primary thymic MALT. No significant correlation between SUVmax and Ki-67 index was observed (r = 0.355, P > 0.05) . Conclusion: Primary thymic MALT lymphoma should be considered in patients with multilocular cystic lesions with different degrees of 18F-FDG uptake in the anterior mediastinum. The results of this study showed no correlation between SUVmax and KI-67 index.